2015
DOI: 10.1371/journal.pone.0130485
|View full text |Cite
|
Sign up to set email alerts
|

The Amyloid Precursor Protein Controls PIKfyve Function

Abstract: While the Amyloid Precursor Protein (APP) plays a central role in Alzheimer’s disease, its cellular function still remains largely unclear. It was our goal to establish APP function which will provide insights into APP's implication in Alzheimer's disease. Using our recently developed proteo-liposome assay we established the interactome of APP's intracellular domain (known as AICD), thereby identifying novel APP interactors that provide mechanistic insights into APP function. By combining biochemical, cell bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…We also tested whether the APP/PIKfyve interplay is conserved in evolution using the C. elegans genetic model. A genetic analysis of the function of the APP orthologue APL-1 revealed that the APL-1 C-terminus is required for PIKfyve (PPK-3 in C. elegans) function required for endosomal homeostasis and neuronal function (45), entirely consistent with the data obtained in mammals.…”
Section: Moreover App and Aplp2 Joint Suppression Sensitised Cells Fsupporting
confidence: 80%
See 1 more Smart Citation
“…We also tested whether the APP/PIKfyve interplay is conserved in evolution using the C. elegans genetic model. A genetic analysis of the function of the APP orthologue APL-1 revealed that the APL-1 C-terminus is required for PIKfyve (PPK-3 in C. elegans) function required for endosomal homeostasis and neuronal function (45), entirely consistent with the data obtained in mammals.…”
Section: Moreover App and Aplp2 Joint Suppression Sensitised Cells Fsupporting
confidence: 80%
“…Using a recently developed methodology for analysing the interactome of the intracellular domains of transmembrane receptors using proteo-liposomes we surprisingly identified the PIKfyve complex as a putative interactor of the APP intracellular domain (45,46). We analysed this interaction in detail and found that the highly conserved YENPTY motif of the APP intracellular domain is crucial for directly binding the Vac14 subunit of the PIKfyve complex (46).…”
Section: The Amyloid Precursor Protein (App) Binds To and Regulates Pmentioning
confidence: 99%
“…In view of the interesting similarities between intracellular trafficking and processing of PMEL and amyloid precursor protein (APP), which is involved in Alzheimer's disease (Bissig et al, 2016;Sannerud et al, 2016), our studies may also have important implications for pathological amyloid formation during Alzheimer's disease. Intriguingly, PIKfyve depletion leads to massive neurodegeneration in individuals with mutations of FIG4 and VAC14 (Baulac et al, 2014;Campeau et al, 2013;Chow et al, 2007;Lenk et al, 2011;Lenk et al, 2016), and PIKfyve influences APP (Balklava et al, 2015;Currinn et al, 2016). It is therefore tempting to speculate that, in neurons, PIKfyve activity regulates the abundance of an amyloidogenic substrate and its proteases in a compartment known to generate the Aβ intracellular pool (Peric and Annaert, 2015;Rajendran and Annaert, 2012;Sannerud et al, 2016).…”
Section: Implications For Pathological Amyloid Formationmentioning
confidence: 99%
“…The protein is involved in regulation of synaptic vesicle exocytosis (Kohli et al, 2012 ) glutamatergic, GABAergic and cholinergic synaptic transmission (Wang et al, 2005 , 2014 ; Schrenk-Siemens et al, 2008 ) and synapse formation (Priller et al, 2006 ). Interestingly, it also regulates endosomal phosphoinositide metabolism and prevents neurodegeneration (Balklava et al, 2015 ), and it interacts with a large variety of survival-related cascades (Russo et al, 2005 ; Venezia et al, 2007 ).…”
Section: Functions Of App and Its Metabolitesmentioning
confidence: 99%